Phytochemicals and Tyrosinase Inhibitory Activity from Piper caninum and Piper magnibaccum - Nur Athirah Hashim; Farediah Ahmad; Wan Mohd Nuzul Hakimi Wan Salleh; Shamsul Khamis (Tabriz University of Medical Sciences, 2019)
Background: Piper species are aromatic plants used as spices in the kitchen, but their secondary metabolites have also shown biological effects on human health. In traditional medicine, Piper species have been used worldwide to treat several diseases such as urological problems, skin, liver and stomach ailments, for wound healing, and as antipyretic and anti-inflammatory agents. In the present study, we attempted to isolate the phytochemicals from Piper caninum and Piper magnibaccum and evaluate their tyrosinase inhibitory activity. Methods: Phytochemical constituents of the extracts were investigated using various chromatographic and spectroscopic methods. The structures of the isolated phytochemicals were established by analysis of their spectroscopic data, as compared to that of reported data. Tyrosinase inhibitory activity was also tested on the extracts and selected compounds using mushroom tyrosinase as the enzyme. Results: Fractionation and purification of the extracts of Piper caninum and Piper magnibaccum afforded nine known compounds which were cepharanone A (1), cepharadione A (2), aristolactam AII (3), 5,7-dimethoxyflavone (4), 24-methylenecycloartan-3-one (5), β-sitosterol (6), piperumbellactam A (7), 24S-ethylcholesta-5,22,25-trien-3β-ol (8) and stigmast-3,6-dione (9). Ethyl acetate extracts from leaves of P. magnibaccum gave the highest inhibition value at 48.35%, while the tested compounds displayed weak tyrosinase activity compared to the positive control, kojic acid. Conclusion: These phytochemical results suggested that the extracts could assist as a potential source of bioactive compounds. Further research is needed in which the extract could possibly be exploited for pharmaceutical use.